Tirodite from Gangpur Group of rocks, India - Mohapatra B. K.; Nayak B. R. (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1997)
Manganese bearing amphibole is recorded in the Mn silicate-oxide rocks of Gangpur Group, India and is identified to be tirodite (Mn-cummingtonitc) with the composition [Mg4.65-4.08, Fe».31-0.01 ;, Mn2.04-1.73, Cao.i<M>.i3, Nao.42-o.37] [OH/Si4Oii]2. Tirodite, coexisting with rhodonite, occurs without carbonate and pyroxene and developed in a low and unbuffered Xco2 system with XMH < 0.32. Appreciable hematite in the assemblage and Fe in tirodite structure attests to an iron rich bulk composition and intermediate fo2 in the amphibolite facies condition.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok